Cross pinning versus lateral pinning in type III supracondylar fracture: a retrospective analysis - Govindasamy, Rajesh; Gnanasundaram, Ramkumar; Kasirajan, Saravanan; Thonikadavath, Fawas; Tiwari, Rajeev K. (International Journal of Research in Orthopaedics, 2016)
Background: The commonly accepted treatment of type III supracondylar fractures of humerus in children is closed reduction percutaneous pinning (CRPP). There is a long debate over stability and complications associated with cross and lateral pinning. The present study compares the functional outcome and complications of both pinning techniques. Methods: A retrospective analysis of results with regard to ulnar nerve injury, carrying angle and range of movements was made in 27 children with lateral pinning and 28 children with crossed pinning was done in our institution. Functional outcome was graded according to Flynn’s criteria and loss of reduction by Skagg’s criteria. Results: There was no statistically significant difference with regard to functional outcome and loss of reduction between the two groups. Iatrogenic ulnar nerve injury (IUNI) occurred in three cases (11%) after crossed pinning in which two had significant palsy, which recovered by three months and the other had only transient paraesthesia. Conclusions: Lateral pinning technique is reliably safe method in terms of stability as it avoids IUNI, we recommend it.